PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA PERMAINAN MEJA GAMBAR PADA SISWA KELAS 1B SD NEGERI KELAYAN 9 - Iis komariah; Patra Aghtiar Rakhman; Nana Hendra Cipta; Jumadi; Dwi Wahyu Candra Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to improve initial reading skills in class 1B students at SD Negeri Kelayan 9 through the media of picture table games. This research is a classroom action research with the subject of class 1B student at SD Negeri Kelayan 9, totaling 25 student. The instrument used are observastion sheets, performance test questions, and reading assessment sheets. The data obtained was analyzed using descriptive teachnique. The result of the research show that the picture table game media can improve the initial reading skills of class 1B students at SD Negeri Kelayan 9. The improvement in intial reading skills can be seen from the result of the research conducted, namely: in cycle I the average score was 75,16 or the number of students who completes totaling 14 (56%) increased to 76,44 wuth the number of students who completed 17 (68%). Then in cycle II number of students who completed it was 20 (80%) with the average scrore increasing to 79,32.